Correlation between albumin serum and frailty in geriatric inpatient and outpatient clinic at Sanglah Hospital Denpasar - Putu Shely Prihastuti Rudy; RA Tuty Kuswardhani; I Gusti Putu Suka Aryana; Nyoman Astika; Ida Bagus Putu Putrawan; Ni Ketut Rai Purnami (DiscoverSys Inc., 2021)
Background. Frailty in the elderly has a bad impact on health, especially in the elderly with acute illness. Elderly with frailty has an increase susceptibility to falls, disability and death. Frailty is a common problem in elderly patients, and hypoalbuminemia suggested to increase the risk of death. This study aimed to determine the relationship between albumin and frailty.Method: A Cross-Sectional Study was conducted from February 2018 to January 2019 at Sanglah Hospital with total 60 patients. Patients were divided into two groups, patients with hypoalbuminemia (albumin < 3.5 g/dL) and patients with normal serum albumin levels (albumin ? 3.5 g/dL). The frailty status assessment was measured with Fried's Frailty Phenotype questionnaire. Chi-square test was used to find the relationship between serum albumin and frailty.Result: We evaluated 60 patients, 36 patients (60%) were male and 24 patients (40%) were female. The age of the study subjects ranged from 62 to 92 years. In this study 26 patients (43.3%) with hypoalbuminemia and 34 patients (56.7%) with normal serum albumin. There were 20 patients (76.9%) with frailty in the hypoalbuminemia group, compared to 11 patients (32.4%) in the group of patients with normal serum albumin. Hypoalbuminemia has a risk of 6.97 times greater frailty compared to normal albumin in elderly patients (p = 0.001).Conclusion: This study exhibited a significant relationship between serum albumin and frailty in elderly admitted to inpatient unit and outpatient clinic. The lower the serum albumin level, the higher the probability of the elderly to experience frailty.